2020
DOI: 10.1111/1475-6773.13321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a standardized community health worker intervention on hospitalization among disadvantaged patients with multiple chronic conditions: A pooled analysis of three clinical trials

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Most CHW-focused trials have not demonstrated significant reductions in hospital readmissions. However, a 2020 pooled analysis of 3 CHW randomized clinical trials 37 found a combined significance in reduced hospital readmissions. The Community Care Transitions intervention used in this study differed from prior studies in that all participants were affiliated with a hospital ACO insurance benefit and had a PCP, a working phone number, and a residential address within a specific radius.…”
Section: Discussionmentioning
confidence: 99%
“…Most CHW-focused trials have not demonstrated significant reductions in hospital readmissions. However, a 2020 pooled analysis of 3 CHW randomized clinical trials 37 found a combined significance in reduced hospital readmissions. The Community Care Transitions intervention used in this study differed from prior studies in that all participants were affiliated with a hospital ACO insurance benefit and had a PCP, a working phone number, and a residential address within a specific radius.…”
Section: Discussionmentioning
confidence: 99%
“…The last strategy maximizes the resources available to GHFP participants through a community health worker (CHW). [17][18][19] The GHFP CHW integrates culturally competent strategies and builds patients' self-sufficiency through a range of activities, including counseling, connections to food banks and government programs, religious services, housing support, health education, and more. The CHW conducts in-hospital needs assessments and meetings with GHFP patients and further assessment at outpatient clinic appointments.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Some programs observed reductions in emergency department visits and hospital admissions 16 . A small number of studies show that CHWs improve the use of appropriate health care services 17,18 and reduce morbidity and mortality for CVD and reduce health disparities when focused on minority communities 19 . Transportation is a SDOH that is a well‐documented barrier to medical care 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…This finding stands at odds with growing enthusiasm in the healthcare sector for such efforts (Gawande, 2011). RCTs for other healthcare organization‐led interventions, such as deployment of community health workers, hospital‐based ride‐share programs, and housing initiatives, have also been conducted in recent years (Chaiyachati et al., 2018; Raven, Niedzwiecki, & Kushel, 2020; Vasan et al., 2020).…”
Section: The Fundamental Value Of Rcts—examples From Health Policymentioning
confidence: 99%